2010
DOI: 10.1111/j.1600-0633.2010.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Population density, growth and reproduction of arapaima in an Amazonian river‐floodplain

Abstract: Arantes CC, Castello L, Stewart DJ, Cetra M, Queiroz HL. Population density, growth and reproduction of arapaima in an Amazonian river‐floodplain. Ecology of Freshwater Fish 2010: 19: 455–465. © 2010 John Wiley & Sons A/S Abstract –  Compensatory density effects are key features of fish population dynamics that remain poorly understood in tropical river‐floodplains. We investigated possible compensatory growth and reproductive processes for a river‐floodplain population of Arapaima sp., an extinction‐prone fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 37 publications
1
72
0
6
Order By: Relevance
“…Silva, Stewart (2006) concluded that black prochilodus in Ecuador form annuli on their otoliths, with the first annulus forming at a SL of about 180 mm (Fig. 2), while others have suggested that black prochilodus and various other fishes in the Central Amazon appear to form bi-annuli on their scales (e.g., Oliveira, 1997 ;Arantes et al, 2010). More research is needed to determine the causes and possible regional variations in translucent zone formation in this and related taxa.…”
Section: Migratory Patterns: a Synthesis Migrations Of Adultmentioning
confidence: 99%
“…Silva, Stewart (2006) concluded that black prochilodus in Ecuador form annuli on their otoliths, with the first annulus forming at a SL of about 180 mm (Fig. 2), while others have suggested that black prochilodus and various other fishes in the Central Amazon appear to form bi-annuli on their scales (e.g., Oliveira, 1997 ;Arantes et al, 2010). More research is needed to determine the causes and possible regional variations in translucent zone formation in this and related taxa.…”
Section: Migratory Patterns: a Synthesis Migrations Of Adultmentioning
confidence: 99%
“…Community-based management programs and protected areas have been effective in facilitating recovery of depleted populations in some areas (Castello et al, 2009;. Recent studies on growth (Arantes et al, 2010), nesting (Castello, 2008a), and migration (Castello, 2008b) also have contributed information necessary for effective conservation and management of Arapaima. For Guyana and many areas of the Amazon basin, however, there are few or no published observations on trophic ecology of Arapaima, and there are few published studies on stable isotope ratios in Arapaima (Forsberg et al, 1993, present only δ…”
Section: Introductionmentioning
confidence: 99%
“…Our results taken as a whole (i.e., isotope values, morphology and diets) suggest that Guyanese Arapaima are more appropriately considered omnivores rather than top predators. That does not take away from their role as consumers in Neotropical ecosystems, however, because their rapid growth (Arantes et al, 2010), large adult size, and relatively low trophic level may allow them to attain very high biomass. It also is evident that there are more than one species of Arapaima in the Amazon River basin (Stewart, 2013, in press), so further studies may reveal that some species are trophic specialists, Arantes, Nov. 2006).…”
mentioning
confidence: 99%
“…Imbiriba (2001) reports that the arapaima's reproduction is probably related with the water-level variation on the floodplains of the Amazon River. Sexual maturity occurs around the third to fifth year of life, when the fish reach an average length of 1.6 m and weigh 40 -50 Kg (Lüling, 1964;Godinho et al, 2005;Arantes et al, 2010). Fontenele (1953) observed that during the spawning season secondary extragenital sexual characteristics develop in the breeders, such as that males begin to present a dark coloring on the upper part of the head and flanks, and the abdomen and caudal peduncle turn reddish.…”
Section: Introductionmentioning
confidence: 99%
“…Even though it has been exploited commercially for many years, much basic life history data are still lacking. However, several recent publications have made significant advances of our understanding of growth and reproductive behavior (Arantes et al, 2010), population dynamics (Coutinho et al, 2010;Castello et al, 2011), spatial and temporal distribution and trophic ecology (Watson et al, 2013) as well as population structuring (Hrbek et al, 2005;Hrbek et al, 2007;Araripe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%